Computer literacy in business schools. (4th August 2014) - Shahabuddin, Syed
The computer explosion began in 1980 with the introduction of microcomputers. As everyone was made aware of the effects of this explosion on their lives, society became concerned with making students learn about computers. Business schools were the first to start teaching introductory courses in data processing. Later, the universities started requiring all students to take a course in computers. At the same time, many high schools also introduced courses in computing. These separate, but similar courses at the secondary and college levels resulted in duplication for some students. To determine how many students are taking or have taken similar courses, I conducted a study of the students taking the Introduction to Data Processing course at Central Michigan University. The study confirms that duplication did occur. The paper discusses the amount of duplication and suggests ways to reduce it.